Preparation method and application of aluminum-zinc-carbon composite material for rapid selective reduction of nitrate
Aluminum-zinc carbon composite materials were prepared by mechanical ball milling, and zero-valent aluminum was activated by local alkaline environment, which solved the problem of low reactivity of aluminum under near-neutral conditions in the prior art, and achieved rapid and efficient selective reduction of nitrate pollutants in water.
Patent Information
- Application Number
- CN202310099879.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-07
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2043-02-07
AI Technical Summary
The prior art is difficult to effectively activate zero-valent aluminum under near neutral conditions, resulting in inefficient efficiency in removing nitrate contaminants in water bodies.
By mechanically ball milling aluminum powder, zinc powder and activated carbon, aluminium zinc carbon composite material is formed, and a local alkaline environment is constructed using the gavarni cathode effect and microscopic primary cells to promote the activation of aluminum and the selective reduction of nitrate.
It realizes rapid selective reduction of nitrate by aluminum-zinc carbon composite materials under normal temperature and pressure, and maintains efficient removal ability within a wide pH range, avoiding secondary pollution.
Smart Images

Figure CN116161766B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of water pollution treatment, and specifically relates to a preparation method of an aluminum-zinc-carbon composite material for rapid and selective reduction of nitrates, and also relates to an application of the aluminum-zinc-carbon composite material for rapid and selective reduction of nitrates in treating nitrate pollutants in wastewater. Background Art
[0002] Nitrate has become the main nitrogen-containing pollutant in groundwater, rivers and lakes. Excessive nitrate concentration in natural water bodies can lead to eutrophication of water bodies, which can easily cause a series of health problems such as cancer when entering the human body.
[0003] The ideal way to remove nitrates from water is to convert them into harmless nitrogen. Currently, a large number of studies have used zero-valent metal chemical reduction methods to remove nitrates from water. It is generally believed that acidic conditions will produce more H* than alkaline conditions, and the reduction of nitrates by active hydrogen (H*) is conducive to the formation of NH bonds, resulting in more ammonia nitrogen production. The most commonly used zero-valent metal iron can only be active under acidic conditions (pH <5), and the nitrogen selectivity of zero-valent iron in reducing nitrates is poor. Zero-valent metal aluminum has extremely high reactivity and chemical amphoteric properties, and studies have shown that zero-valent aluminum has better nitrogen selectivity in reducing nitrates under alkaline conditions than zero-valent iron. However, the dense oxide layer on the surface of aluminum powder hinders electron release, greatly limiting the reactivity of zero-valent aluminum, resulting in extremely low removal efficiency of zero-valent aluminum for pollutants under near-neutral conditions.
[0004] Therefore, it is of great significance to develop a new technology to achieve continuous activation of zero-valent aluminum and efficient and selective reduction of nitrates. Summary of the invention
[0005] One of the purposes of the present invention is to provide a method for preparing an aluminum-zinc-carbon composite material that can self-construct a local alkaline environment to promote the activation of zero-valent aluminum, so that the activated zero-valent aluminum continuously outputs electrons and quickly and selectively reduces nitrate to nitrogen.
[0006] A second object of the present invention is to provide an aluminum-zinc-carbon composite material for rapid and selective reduction of nitrates for use in treating wastewater containing nitrate pollutants.
[0007] The technical solution adopted by the present invention to achieve one of the purposes is: to provide a preparation method of an aluminum-zinc-carbon composite material for rapid and selective reduction of nitrates, comprising the following steps: placing aluminum powder, zinc powder, activated carbon and ball milling beads in a ball milling jar, sealing and evacuating the jar, and then filling with inert gas; performing ball milling treatment under an inert atmosphere to obtain the aluminum-zinc-carbon composite material.
[0008] In the present invention, aluminum powder, zinc powder and activated carbon are mechanically ball-milled to obtain an aluminum-zinc-carbon composite material. Aluminum powder, zinc powder and ball milling beads abrade the metal surface during high-speed collision to form dislocation defects, thereby destroying the passivation layer on the surface of the metal powder and exposing a fresh active metal surface. Among them, the carbon material provides a galvanic cathode effect to ensure the alkaline dissolution of aluminum, and also provides a reduction site for highly selective reduction of nitrates to nitrogen. The addition of zinc powder can bring the following advantages: on the one hand, the zinc powder with strong activity after ball milling can construct a large number of microscopic primary cells with activated carbon, promote the formation of local alkalinity, and thus promote the activation of aluminum; on the other hand, zinc can reduce nitrates to nitrites, thereby further improving the nitrate reduction rate.
[0009] Furthermore, the purity of the aluminum powder is 95-99%, and the particle size is 50-2000 mesh. The purity of the zinc powder is 90-99%, and the particle size is 50-1000 mesh. In the present invention, the storage and transportation process of metal powder with too small particle size is risky, and the metal powder with too large particle size has a small specific surface area and low reaction activity.
[0010] Furthermore, the activated carbon is selected from one or more combinations of coconut shell activated carbon, wood activated carbon, fruit shell activated carbon and coal activated carbon. Such activated carbon materials have a large specific surface area and rich functional groups.
[0011] Furthermore, the mass ratio of aluminum powder, zinc powder and activated carbon is (1-3): (0.05-1): (1-10). In the present invention, the amount of zinc powder used is lower than that of aluminum powder and activated carbon, which can reduce the possibility of secondary pollution and reduce costs. Preferably, the mass ratio of aluminum powder, zinc powder and activated carbon is (1-3): 0.4: (5-8).
[0012] Furthermore, the inert atmosphere is selected from one of argon, nitrogen or helium.
[0013] Furthermore, the mass ratio of the ball milling beads to the material addition amount is (10-100):1. Preferably, the mass ratio of the ball milling beads to the material addition amount is 20:1. The material of the ball milling beads is selected from one or more of zirconia, agate, corundum, and stainless steel, and the particle size of the ball milling beads is 6-20 mm. In some preferred embodiments, the ball milling beads are composed of ball milling beads with particle sizes of 6 mm, 10 mm, and 15 mm, respectively, in a quantitative ratio of 15:5:1.
[0014] Furthermore, the ball milling equipment is a planetary ball mill; the ball milling speed is 200-500 rpm, and the ball milling time is 1-20 hours. Preferably, the ball milling speed is 400 rpm, and the ball milling time is 3 hours.
[0015] Furthermore, the storage condition of the aluminum-zinc-carbon composite material is: storage under nitrogen protection conditions.
[0016] The technical solution adopted by the present invention to achieve the second purpose is: to provide an aluminum-zinc-carbon composite material prepared by the preparation method described in one of the purposes of the present invention and to use it in removing nitrate pollutants in wastewater.
[0017] Furthermore, the dosage of the aluminum-zinc-carbon composite material in the wastewater containing nitrate is 1 to 30 g / L.
[0018] Furthermore, the pH of the wastewater is 3-11, and the reaction temperature is 10-30°C.
[0019] The aluminum-zinc-carbon composite material prepared by the present invention reduces nitrate, and mainly undergoes a two-stage reaction process:
[0020] In the first stage, the activated carbon material has a large specific surface area and the ability to transfer electrons, and can form a microscopic corrosion primary cell with the fresh aluminum and zinc after ball milling in the aqueous solution. As shown in formula 1-3:
[0021] Anode reaction: Al-3e - =Al 3+ E 0 (Al 3+ / Al)=-1.66V (Formula 1)
[0022] Zn-2e - =Zn 2+ E 0 (Zn 2+ / Zn)=-0.76V (Formula 2)
[0023] Cathode reaction: 2H2O+2e - =H2+2OH - (Formula 3)
[0024] The zinc powder after ball milling is highly active and reacts rapidly when put into the solution. The aluminum and zinc materials as the anode are rapidly dissolved and release a large amount of electrons. The carbon surface as the cathode undergoes a hydrolysis reaction, and the OH - It will cause the pH of the carbon surface to rise, forming a local alkaline environment, which constitutes the "Galvanic cathode effect". In addition, the zinc with strong activity after ball milling can reduce nitrate to nitrite. As the local alkalinity rises, the oxide layer on the aluminum surface gradually dissolves, thereby promoting the continuous activation of zero-valent aluminum and the output of electrons. At the same time, the alkaline environment formed will promote the precipitation of dissolved zinc ions to avoid secondary pollution.
[0025] In the second stage, under local alkaline conditions, the generation of H* is suppressed, and the activated carbon with a large specific surface area serves as the cathode, which efficiently and selectively reduces nitrate and nitrite to nitrogen through a direct electron transfer process.
[0026] Furthermore, the rich functional groups on the surface of activated carbon have a certain ability to buffer the pH of the solution. At the same time, aluminum and its various hydrolysis products can stabilize the pH of the solution. Therefore, when using this material to treat pollutants, the pH of the solution can be effectively maintained to prevent the solution from becoming over-alkaline.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The present invention provides a method for preparing an aluminum-zinc-carbon composite material for rapid selective reduction of nitrates. The carbon material, aluminum powder and zinc powder used are all industrial-grade raw materials. The materials are cheap and easy to obtain, can be used on a large scale, and can effectively control the cost of treating wastewater. The preparation method is carried out at room temperature and pressure, the synthesis process is simple, the reaction conditions are mild, and it is suitable for industrial preparation and production.
[0029] (2) The aluminum-zinc-carbon composite material for rapid selective reduction of nitrates prepared by the present invention is put into wastewater containing nitrates, and the galvanic cathode effect can be used to form a local alkaline environment to promote aluminum activation. Zero-valent aluminum can be continuously dissolved without passivation, which effectively solves the practical problem of zero-valent aluminum materials in the field of environmental remediation. At the same time, after the alkaline environment is formed, zinc ions will precipitate rapidly to avoid secondary pollution. Furthermore, the aluminum-zinc-carbon composite material can achieve efficient selective reduction of nitrates on the surface of activated carbon through a direct electron transfer process by self-constructing a local alkaline environment.
[0030] (3) The aluminum-zinc-carbon composite material for rapid and selective reduction of nitrate prepared by the present invention can still maintain good metal activity and pollutant removal capabilities under a wide pH range (3 to 11), dissolved oxygen, and interference from multiple ions, and can be applied to a variety of water body restoration scenarios, with broad prospects for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A schematic diagram of the principle of the aluminum-zinc-carbon composite material provided by the present invention to self-construct an electrochemical cathode local alkaline environment and efficiently and selectively reduce nitrate to nitrogen;
[0032] Figure 2 The raw materials used in Example 1 of the present invention and the photos of the aluminum-zinc-carbon composite material obtained;
[0033] Figure 3The figure is a diagram showing the effect of the aluminum-zinc-carbon composite material prepared in Example 1 of the present invention on treating nitrate-containing wastewater; wherein (a) is a graph showing the change of nitrate and nitrite concentrations in the wastewater over time; and (b) is a graph showing the change of pH value and soluble zinc concentration in the wastewater over time. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0036] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited thereto.
[0037] The raw materials and main parameters involved in Examples 1-7 and Comparative Examples 1-3 of the present invention are shown in Table 1 below.
[0038] Table 1
[0039]
[0040] Among the raw materials in the above table, the particle size of aluminum powder is 80-150 μm, and the purity is 99%; the particle size of zinc powder is 10-100 μm, and the purity is 98%.
[0041] Example 1
[0042] In a stainless steel ball mill with a volume of 100mL, add 70g of ball mill beads (agate beads) with diameters of 15mm, 10mm, and 6mm in a ratio of 1:5:15; weigh 2.5g coconut shell activated carbon, 0.5g aluminum powder, and 0.5g zinc powder into the ball mill respectively, that is, the mass ratio between aluminum, zinc, and carbon is 1:1:5, and the mass ratio of the added material to the ball mill beads is 1:20. After the closed ball mill is evacuated, argon gas is introduced as a protective gas, and the ball mill is placed in a planetary ball mill with a speed of 400rpm and a continuous ball milling time of 3h. After ball milling, take out the obtained aluminum-zinc-carbon composite material and place it under nitrogen protection.
[0043] The raw materials and the aluminum-zinc-carbon composite material obtained in Example 1 are as follows: Figure 2 As shown, aluminum and zinc are well dispersed in the activated carbon after ball milling.
[0044] Example 2
[0045] On the basis of Example 1, an aluminum-zinc-carbon composite material (Al:Zn:AC=1:1:3) was prepared according to the raw material ratios and parameters shown in Table 1, while other conditions remained unchanged, and the product was stored in nitrogen.
[0046] Example 3
[0047] On the basis of Example 1, an aluminum-zinc-carbon composite material (Al:Zn:AC=1:0.5:5) was prepared according to the raw material ratios and parameters shown in Table 1, while other conditions remained unchanged, and the product was stored in nitrogen.
[0048] Example 4
[0049] On the basis of Example 1, an aluminum-zinc-carbon composite material (Al:Zn:AC=1:0.2:5) was prepared according to the raw material ratios and parameters shown in Table 1, while other conditions remained unchanged, and the product was stored in nitrogen.
[0050] Example 5
[0051] On the basis of Example 1, an aluminum-zinc-carbon composite material (Al:Zn:AC=1:0.1:5) was prepared according to the raw material ratios and parameters shown in Table 1, while other conditions remained unchanged, and the product was stored in nitrogen.
[0052] Example 6
[0053] On the basis of Example 1, an aluminum-zinc-carbon composite material (Al:Zn:AC=1:0.05:5) was prepared according to the raw material ratios and parameters shown in Table 1, while other conditions remained unchanged, and the product was stored in nitrogen.
[0054] Example 7
[0055] On the basis of Example 1, an aluminum-zinc-carbon composite material (Al:Zn:AC=1:0.5:8) was prepared according to the raw material ratios and parameters shown in Table 1, while other conditions remained unchanged, and the product was stored in nitrogen.
[0056] Comparative Example 1
[0057] In a stainless steel ball mill with a volume of 100 mL, add ball milling beads (agate beads) with diameters of 15 mm, 10 mm, and 6 mm in a ratio of 1:5:15; weigh 1.5 g of coconut shell activated carbon into the ball mill, and the mass ratio of the added material to the ball milling beads is 1:20. After the closed ball mill is evacuated, argon gas is introduced as a protective gas, and the ball mill is placed in a planetary ball mill with a speed of 400 rpm and a continuous ball milling time of 3 hours. After ball milling, take out the obtained carbon material and place it under nitrogen protection.
[0058] Comparative Example 2
[0059] In a stainless steel ball mill with a volume of 100 mL, ball mill beads (agate beads) with diameters of 15 mm, 10 mm, and 6 mm were added in a ratio of 1:5:15; 1.5 g coconut shell activated carbon and 0.5 g zinc powder were weighed into the ball mill respectively, that is, the mass ratio between zinc and carbon was 1:3, and the mass ratio between the added material and the ball mill beads was 1:20. After the closed ball mill was evacuated, argon gas was introduced as a protective gas, and the ball mill was placed in a planetary ball mill with a speed of 400 rpm and a continuous ball milling time of 3 hours. After ball milling, the obtained zinc-carbon material was taken out and placed under nitrogen protection.
[0060] Comparative Example 3
[0061] In a stainless steel ball mill with a volume of 100mL, ball mill beads (agate beads) with diameters of 15mm, 10mm, and 6mm were added in a ratio of 1:5:15; 1.5g coconut shell activated carbon and 0.5g aluminum powder were weighed into the ball mill respectively, that is, the mass ratio between aluminum and carbon was 1:3, and the mass ratio between the added material and the ball mill beads was 1:20. After the closed ball mill was evacuated, argon gas was introduced as a protective gas, and the ball mill was placed in a planetary ball mill with a speed of 400rpm and a continuous ball milling time of 3h. After ball milling, the obtained aluminum-carbon material was taken out and placed under nitrogen protection.
[0062] Application Example 1
[0063] Prepare 100mL of 30mg / L NO3 - -N simulated wastewater, without adjusting the initial pH of the solution (about 6.7). The aluminum-zinc-carbon composite material prepared in Example 1 was added to the serum bottle at a dosage of 20 g / L. The serum bottle was sealed and placed in a constant temperature water bath oscillator, the temperature was set to 25°C, the speed was set to 200 rpm, and the reaction time was 80 min. 1.5 mL was sampled regularly and filtered with a 0.22 micron polyethersulfone filter head, the nitrate and nitrite concentrations were detected by ion chromatography, the ammonia nitrogen concentration was detected by ultraviolet spectrophotometer, and the zinc ion concentration was detected by atomic absorption spectrometer.
[0064] like Figure 3 As shown in (a), the aluminum-zinc-carbon composite material prepared in Example 1 can completely remove 30 mg / L of NO3 in 60 minutes. - -N, a nitrogen selectivity of more than 87.6% can be obtained. Nitrite reached a peak of 5.7 mg / L at 40 min and then dropped to zero.
[0065] like Figure 3As shown in (b), as the reaction proceeds, the solution pH rises and stabilizes at around 8.5. The concentration of soluble zinc rises to 24.2 mg / L at 20 min and rapidly drops below the detection limit at 40 min. This is because under this pH condition, soluble zinc will form hydroxide precipitation and will not cause secondary dissolution pollution.
[0066] Application Example 2
[0067] Prepare multiple 100mL portions of 30mg / L NO3 - -N simulated wastewater, without adjusting the initial pH of the solution (about 6.7), 20g / L of the aluminum-zinc-carbon composite material (Al:Zn:AC=1:1:3) prepared in Example 2, and the carbon, zinc-carbon, and aluminum-carbon materials prepared in Comparative Examples 1-3 (the amount added is consistent with the mass of each component contained in the aluminum-zinc-carbon composite material in Example 2) were added to each serum bottle. The serum bottle was sealed and placed in a constant temperature water bath oscillator, the temperature was set to 25°C, the speed was set to 200rpm, and the reaction time was 10h. 1.5mL was sampled regularly and filtered with a 0.22 micron polyethersulfone filter head, the nitrate and nitrite concentrations were detected by ion chromatography, and the ammonia nitrogen concentration was detected by ultraviolet spectrophotometer. The results are shown in Table 2 below.
[0068] Table 2
[0069]
[0070] As shown in Table 2, the nitrate removal rates of the carbon, aluminum-carbon and zinc-carbon materials prepared in Comparative Examples 1-3 were all lower than 7%, while the nitrate removal rate of the aluminum-zinc-carbon composite material prepared in Example 2 reached 100%, and the nitrogen selectivity was as high as 84.1%.
[0071] Application Example 3
[0072] Prepare 100mL of 30mg / L NO3 - -N simulated wastewater was prepared in multiple portions without adjusting the initial pH of the solution (about 6.7). 20 g / L aluminum-zinc-carbon composite materials with different aluminum-zinc mass ratios prepared in Examples 3-6 were added to the serum bottles. The serum bottles were placed in a constant temperature water bath oscillator, the temperature was set to 25 ° C, the speed was set to 200 rpm, and the reaction time was 2 hours. 1.5 mL was sampled regularly and filtered with a 0.22 micron polyethersulfone filter head. The concentrations of nitrate and nitrite were detected by ion chromatography, and the concentration of ammonia nitrogen was detected by ultraviolet spectrophotometer. The results are shown in Table 3 below.
[0073] Table 3
[0074]
[0075] It can be seen from the above table that carbon composite materials with different aluminum-zinc mass ratios (Al:Zn=2~20:1) can achieve a nitrate removal rate of more than 88% within 2 hours, and the nitrogen selectivity exceeds 70%.
[0076] Application Example 4
[0077] Prepare 100mL of 30mg / L NO3 - -N simulated wastewater, add 20g / L, 15g / L, 10g / L, 5g / L, 1g / L of the aluminum-zinc-carbon composite material (Al:Zn:AC=1:0.5:8) prepared in Example 7 to the serum bottle respectively. The serum bottle was placed in a constant temperature water bath oscillator, the temperature was set to 25°C, the speed was set to 200rpm, and the reaction time was 3h. 1.5mL was sampled regularly and filtered with a 0.22 micron polyethersulfone filter head, the nitrate and nitrite concentrations were detected by ion chromatography, and the ammonia nitrogen concentration was detected by ultraviolet spectrophotometer. The test results are shown in Table 4 below.
[0078] Table 4
[0079]
[0080] It can be seen from the above table that the aluminum-zinc-carbon composite material prepared in the present invention has the advantage of rapid and efficient selective reduction of nitrate to nitrogen. Under the condition of an addition amount of 1 to 20 g / L, a nitrate removal rate of more than 90% can be obtained, and the nitrogen selectivity reaches more than 76%.
[0081] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of the specification of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an aluminum-zinc-carbon composite material for rapid and selective reduction of nitrates, characterized in that: The following steps are involved: Aluminum powder, zinc powder, activated carbon and ball mill beads are placed in a ball mill according to a mass ratio of (1-3): (0.05-1): (1-10), and the jar is sealed and evacuated, followed by filling with inert gas; ball milling is performed under an inert atmosphere to obtain an aluminum-zinc-carbon composite material.
2. The preparation method according to claim 1, characterized in that: The purity of the aluminum powder is 95-99%, and the particle size is 50-2000 meshes.
3. The preparation method according to claim 1, characterized in that: The purity of the zinc powder is 90-99%, and the particle size is 50-1000 meshes.
4. The preparation method according to claim 1, characterized in that: The activated carbon is selected from one or more combinations of coconut shell activated carbon, wood activated carbon, fruit shell activated carbon and coal activated carbon.
5. The preparation method according to claim 1, characterized in that: The inert atmosphere is selected from one of argon, nitrogen or helium.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the ball milling beads to the material addition amount is (10~100):
1.
7. The preparation method according to claim 1, characterized in that: The ball milling beads are composed of ball milling beads with particle sizes of 6 mm, 10 mm and 15 mm in a quantity ratio of 15:5:
1.
8. The preparation method according to claim 1, characterized in that: The rotation speed of the ball milling treatment is 200-500 rpm, and the time of the ball milling treatment is 1-20 hours.
9. Application of an aluminum-zinc-carbon composite material for rapid and selective reduction of nitrates in removing nitrate pollutants from wastewater, characterized in that: The aluminum-zinc-carbon composite material is prepared by the preparation method according to any one of claims 1 to 8; the dosage of the aluminum-zinc-carbon composite material in wastewater is 1 to 30 g / L.
Citation Information
Patent Citations
Method for zero-valent metal and carbon combination internal electrolysis catalysis reduction of nitrate nitrogen in water zero-valent metal and carbon combination
CN103193298A
Preparation method for preparing zero-valent aluminum and iron-based spinel composite material based on ball milling and application of zero-valent aluminum and iron-based spinel composite material
CN114405612A